An Analysis Of 5.8 GHz Microwave Doppler Radar For Heartbeat Detection - Othman, Mohd Azlishah; Sinnappa, Mohan; Azman, Hazwani; Abd Aziz, Mohamad Zoinol Abidin; Husain, Mohd Nor; Ismail, Mohd Muzafar; Sulaiman, Hamzah Asyrani; Misran, Mohamad Harris; Meor Said, Maizatul Alice; Ramlee, Ridza Azri (Wydawnictwo SIGMA, 2013)
Non-contact heartbeat detection is one of the current emerging technologies in various fields, especially in health care service. Proper distance and power level is more preferable in a system design to provide better health care monitoring system. The purpose of this paper is to present a filtering technique using Matlab, and the correlation in distance and power level of heartbeat detection based on Doppler Effect principle. An experiment was conducted at 5.8GHz with varied the distance and power level. A comparative study is carried out based on experimental results.